IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI AKADEMIK MAHASISWA PENDIDIKAN MATEMATIKA MENGGUNAKAN METODE CHAID - Hulu, Krisnatal; Zega, Yulisman; Mendrofa, Ratna Natalia; Mendrofa, Netti Kariani (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aims to identify the factors influencing the academic achievement of mathematics education students at Nias University. The researcher employed the CHAID method to address this research problem. Data was collected through an online survey distributed to Mathematics Education students from the 2020 to 2023 cohorts who were in their second to eighth semesters. The analysis results indicate that both the type of residence and gender significantly influence students' academic achievement. The analysis revealed that students who chose to live in dormitories or with their parents significantly obtained higher Grade Point Averages (GPAs) compared to those who chose to live with guardians or in rented accommodations. The findings of this study can be utilized to design more effective intervention programs to enhance students' academic achievement, particularly for those who choose specific types of residence. A deeper understanding of the factors influencing academic achievement is expected to serve as a foundation for efforts to improve the quality of education at Nias University..